Boiled milk, food safety and the risk of exposure to milk borne pathogens in informal dairy markets in Tanzania - Kilango, K.; Makita, K.; Kurwijila, Lusato R.; Grace, Delia (2012)
In Tanzania, more than 80% of the milk consumed is marketed as loose, raw milk. On the other hand, the practice of boiling milk before consumption is very common. The study was carried out to establish food safety status of informally marketed milk including boiled milk. Milk samples were collected in four wards of Temeke Municipality of Dar es salaam. A total of 69, 44 and 7 milk samples were collected from randomly selected farmers, milk kiosks and all milk vendors. The bacteriological quality of the milk with respect to Total Bacterial Counts (TBC) and Escherichia coli was lower at milk vendors level than farm and milk kiosk. The TBC of raw milk was found to be an average of 2.8 ± 0.98 x 106 cfu/ml at producer level, 3.4 ± 2.6 x 107 cfu/ml at vendor’s level and 4.8 ± 3.3 x 107 cfu/ml at kiosk level. TBC values for kiosk milk boiled and served hot was also determined and found to be an average of 3.7 ± 2.3 x 105 cfu/ml. The samples were analysed for presence of toxin producing Staphylococcus aureus. Exposure assessment showed that the probability of purchasing boiled milk contaminated with S. aureus, served hot at kiosks was 0.227 (90%CI: 0.062-0.436). It was estimated that every day, 953 (90%CI: 718-1,249) people purchase milk from kiosks in peri-urban Temeke, and among them, 217 (90%CI: 62-427) people were likely to purchase contaminated milk. The present study found that while boiling made milk generally safer by killing most pathogens, it still carries the risk of consumer exposure to pathogenic bacteria due to possible recontamination.